Political Discipline and Catholic Ceremony in Manchukuo:Taking the Record of Manchuria Monthly as an Example - XU, Bingsan; ZHAO, Yang (Journal of Research for Christianity in China (JRCC), 2023)
During Manchukuo period, Japanese Puppet Regime often dispatched political organizations and officials to preach Japanese political ideas at various Catholic ceremonies. Catholic community were forced to worship Imperial City, Japanese and Manchukuo emperor, Manchukuo flag, and sing Manchukuo song on the occasions. Cooperating with the authority, Catholic clerics combined Catholic doctrines with Japanese policies and sang high praise for Manchukuo. They asked Catholics to obey and service Manchukuo and Japan. Catholic communities were also obliged to participate in various political celebrations, which were most frequent in Catholic schools. Part of rituals, such as shrine worship, have obvious idolatry elements. The phenomenon not only reflects that Japanese and Puppet Regime tried to utilize religious organizations, but also indicate that the Holy See cooperated with Japan actively in order to keep Catholic mission benefits.
Keywords: Manchukuo, the Catholic Churches, Catholic rituals, the relationship between politics and religion